A Strong Law of Large Numbers for Weighted Sums of i.i.d. Random Variables under Capacities - Defei Zhang; Ping He (Journal of Applied Mathematics)
With the notion of independent identically distributed (i.i.d.) random variables under sublinear expectations initiated by Peng, a strong law of large numbers for weighted sums of i.i.d. random variables under capacities induced by sublinear expectations is obtained.